Hair analysis for drugs of abuse. Plausibility of interpretation - Balíková, Marie (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2005)
Over more than 20 years hair analysis for drugs has been gaining increasing attention and recognition in various toxicological fields as preemployment and employment screening, forensic sciences, doping control of banned substances, clinical diagnostics in health problems. Hair analysis for drugs can expand the toxicological examination of conventional materials and thus contribute with additional important information to the complex evaluation of a certain case. Hair is a unique material for the retrospective investigation of chronic drug consumption, intentional or unintentional chronic poisoning in criminal cases, gestational drug exposure or environmental exposure to pollutants and adulterants and with specific ultrasensitive procedures allow to demonstrate even a previous single dose administration in a very low amount. Assuming the ideal hair steady and uniform growth, segmental hair analysis can provide the information about the time course of the substance use or exposure. However, the physiological background of hair growth, mechanisms of drug incorporation are not simple, not yet understood in full details and need not be evaluated exactly in all cases. The hair sampling, storage, sample preparation, analytical performance themselves are also very important for final results. Different laboratory attitudes can produce different results. The full information on circumstances of the case examined must be taken into account during interpretation. The pitfalls in hair analysis should be known and avoided to assure the responsible and correct interpretation of laboratory results adequate to an individual case.
Keywords: soudní toxikologie; vlasy, chlupy; lidé; otrava; Hair; Humans; Forensic Toxicology; odhalování abúzu drog; Substance Abuse Detection; Poisoning